2016
DOI: 10.1074/jbc.m116.753566
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Glycine Mutations in the Fibronectin-binding Sequence of Collagen

Abstract: Collagen and fibronectin (Fn) are two key extracellular matrix proteins, which are known to interact and jointly shape matrix structure and function. Most proteins that interact with collagen bind only to the native triple-helical form, whereas Fn is unusual in binding strongly to denatured collagen and more weakly to native collagen. The consequences of replacing a Gly by Ser at each position in the required (Gly-Xaa-Yaa) Fn-binding sequence are probed here, using model peptides and a recombinant bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Recent studies indicate the importance of the glycine substitutions in changing stability of the triple helix and interactions of collagen with other proteins of extracellular matrix like fibronectin etc. (Ito et al, ; Chhum et al, ). Mutations of COL2A1 may result in conditions other than skeletal dysplasias (Kannu, Bateman, Belluoccio, Fosang, & Savarirayan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate the importance of the glycine substitutions in changing stability of the triple helix and interactions of collagen with other proteins of extracellular matrix like fibronectin etc. (Ito et al, ; Chhum et al, ). Mutations of COL2A1 may result in conditions other than skeletal dysplasias (Kannu, Bateman, Belluoccio, Fosang, & Savarirayan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that substitution of these integral Gly residues causes structural deformities to the triple helix, and the extent of triple-helix destabilization depends on the amino acid substituted (30,31) and the surrounding sequence context (32)(33)(34)(35)(36). Recently, elegant studies have investigated the impact of Gly 3 Xaa mutations near integrinbinding sites in collagen I (31, 37) using recombinant bacterial collagen systems, which can incorporate long spans of collagenlike sequence and can probe selective mutation sites.…”
mentioning
confidence: 99%
“…The synthetic peptides and the phosphorylation products were analyzed with a MALDI-TOF Microflex LT instrument (Bruker, Billerica, MA) in positive ion mode. Samples were mixed with MALDI matrix (a saturated sinapinic acid solution in 50% (v/v) acetonitrile and 0.3% (v/v) trifluoroacetic acid) in a 1:4 ratio, and 1 mL of the peptide-containing matrix was pipetted onto a MALDI target plate and allowed to dry, as previously described (20). It was noted that each peptide produced multiple peaks, one at the expected mass of the peptide as well as a second peak at a higher molecular weight that corresponded to the mass of the peptide plus an associated cation (either sodium or potassium).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…MD simulations were carried out to investigate whether the bulky and charged pSer within the Gly-Xaa-Yaa repeating sequence of peptide pSer546 could be incorporated into a standard triple helix. The sequence of the phosphorylated peptide was constructed into a triple helix (20). MD simulations were carried out for 100 ns at 300 K using the Amber99SB force field and TIP3P water model, following a previously described simulation protocol (3,20).…”
Section: Simulations Of the Collagen Triple Helix With Psermentioning
confidence: 99%
See 1 more Smart Citation